Isolation of plant growth-promoting rhizobacteria from wild-simulated ginseng and evaluation of soil health following its application in the field - Lee, Seok Hui; Yun, Yeong-Bae; Kim, Dae Sol; Park, Myeongbin; Um, Yurry; Kang, Jun Won (Frontiers in Microbiology, 2025)
Wild-simulated ginseng must be cultivated at natural forest sites without artificial structures, chemical fertilizers, or pesticides to qualify for certification. However, its extended cultivation period makes stable production challenging, necessitating effective strategies to enhance early growth and yield. In this study, we evaluated the ability of five bacterial strains isolated from the rhizosphere of wild-simulated ginseng to promote initial growth and development. The strains exhibited diverse functional traits, including indole-3-acetic acid (IAA) production, phosphate solubilization, siderophore production, and enzymatic activities such as protease and cellulase. Antifungal activity, however, was primarily observed in strains 79 and 81. We inoculated field-grown ginseng plants with each strain at biweekly intervals for a total of seven applications. Inoculation with strain 75 (Pseudomonas frederiksbergensis) significantly increased shoot dry weight by 48.9% and root biomass by 37.0% relative to uninoculated controls (p < 0.05). Strain 81 (Paenibacillus terrae) promoted stem elongation, whereas strain 89 (Paraburkholderia madseniana) reduced leaf size. Soil analysis showed that strain 75 and 77 plots maintained higher organic matter, phosphorus, calcium, and cation exchange capacity, whereas strains 79, 81, and 89 had lower values. Metagenomic analysis revealed a marked enrichment of the order Pseudomonadales and the maintenance or enhancement of bacterial alpha diversity (Chao1 and PD indices), suggesting a stable and resilient microbial ecosystem. Functional profiling revealed enhancements in nitrogen fixation and nutrient cycling pathways. We determined statistical significance using a t-test and one-way ANOVA with Duncan’s multiple range test (p < 0.05). In contrast, strains 79 (Paraburkholderia terricola), 81 (Paenibacillus terrae), and 89 (Paraburkholderia madseniana) did not elicit significant growth responses. Our findings indicate that P. frederiksbergensis (strain 75) is a promising plant growth-promoting rhizobacterium for wild-simulated ginseng, offering a biologically based approach for improving early-stage development under forest cultivation conditions.